Abstract 12836: Predictors of Recurrent Pericardial Effusion in Cancer Patients Requiring Pericardiocentesis - AHMED, TALHA; Safdar, Ayesha; Song, Juhee; Banchs, Jose; Kim, Peter; Palaskas, Nicolas L; Iliescu, Cezar (Circulation (New York, N.Y.), 2021)
IntroductionPericardial effusion (PE) is a common manifestation of various malignancies and tends to recur in a subset of patients requiring recurrent PC. HypothesisWe sought to evaluate the factors determining the recurrence of PE in certain subsets of patients. MethodsAll data pertaining to PC for large PE in a cancer patient population performed and enrolled over a decade 2010-2020 in a Cancer Center Pericardiocentesis Registry were analyzed. Patient characteristics were summarized using descriptive statistics (Mean (SD) for continuous variables and frequency (%) for categorical variables. Time to first recurrent PC was defined as time interval from index PC to first recurrent PC. Fine-Gray models were used to identify risk factors associated with incidence of recurrent PC while Cox regression models were used to identify risk factors associated with risk of death. ResultsData set included 418 subjects with index PC and 65 (16%) had recurrent PC while 353 (84%; 286 died without recurrent PC and 67 were alive without recurrent PC) did not have recurrent PC. Descriptive statistics for the entire group are described in table 1. Younger age, elevated creatinine, non-colon cancer, established advanced-stage cancer, presence of cardiac metastasis, and non-colon cancer (P=<0.05) were associated with increased incidence of recurrence of pericardiocentesis. The risk of death was higher in patients with older age, malignant effusion by cytology, no use of anti-inflammatory agents, and primary lung cancer (p=<0.05). The cumulative incidence of recurrent pericardiocentesis at 12 months was 15 % and did not differ much at 60 (16 %). ConclusionsPatients with advanced-stage cancer are more likely to present with recurrent pericardial effusion and tamponade. Pericardiocentesis appears to have a palliative role in this population with increased disease and treatment-related mortality.